2020
DOI: 10.1111/bju.15002
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer in kidney transplant recipients – a nationwide register study

Abstract: ConclusionsThis Swedish nationwide, register-based study gave no indication that immunosuppression after kidney transplantation increases the risk of prostate cancer or adversely affects prostate cancer outcomes. The study suggests that men with untreated low-grade prostate cancer can be accepted for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 34 publications
1
34
0
1
Order By: Relevance
“…Given this background, the utility of PCa screening, performed in all candidates to renal transplantation to ensure appropriate kidney allocation, remains still debated. Bratt et al in their national renal register and PCa register identified 133 KT recipients, transplantated before 1990s when PSA testing became common, and concluded their analysis that immunosuppression after KT did not increase the risk of PCa or adversely affected PCa outcomes ( 30 ). In our study, PCa incidence for RTRs was 3.24%, slightly higher when compared to previously published reports where incidence ranged from 0.3 to 2% ( 7 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given this background, the utility of PCa screening, performed in all candidates to renal transplantation to ensure appropriate kidney allocation, remains still debated. Bratt et al in their national renal register and PCa register identified 133 KT recipients, transplantated before 1990s when PSA testing became common, and concluded their analysis that immunosuppression after KT did not increase the risk of PCa or adversely affected PCa outcomes ( 30 ). In our study, PCa incidence for RTRs was 3.24%, slightly higher when compared to previously published reports where incidence ranged from 0.3 to 2% ( 7 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR) inhibitor, sirolimus, has been associated with lower risk of malignancy (HR 0.60, 95% CI 0.39-0.93) with an even greater reduction in patients switching from other regimens to sirolimus [13]. In a recent study, Bratt and colleagues demonstrated that immunosuppressive therapy did not increase the overall risk of PCa in RTRs [14].…”
Section: Renal Transplantation and Prostate Cancermentioning
confidence: 99%
“…To summarise, this study [1], and others before that, suggests that immunosuppression after kidney transplantation is unlikely to adversely affect prostate cancer initiation or progression. Men with low‐risk prostate cancer should be considered for transplantation without first undergoing definitive therapy.…”
mentioning
confidence: 94%
“…The basis for this approach stems from the theoretical higher risk of disease progression and ultimately mortality on immunosuppression. In this issue of the BJU International , Bratt et al [1] challenge these assumptions and report on the outcomes of kidney transplant recipients diagnosed with prostate cancer. First, they found no difference in prostate cancer incidence, suggesting that transplant recipients, despite being immunosuppressed, are not at higher risk of prostate cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation